Efektivitas Pelaksanaan Tugas Satuan Polisi Pamong Praja dalam Penertiban Asrama/Pemondokan di Kecamatan Ende Tengah Kabupaten Ende - Don Alexander Intan DVG; Saryono Yohanes; Hernimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the effectiveness of the implementation of the duties of the civil police unit in the management of dormitories/lodging in Central Ende District, Ende Regency. This research is an empirical juridical research that uses three approaches, namely the socio-legal approach, the conceptual approach and the doctrinal approach using primary data and secondary data collected using observation, interview and literature study methods. This study uses a method of processing legal materials which is processed in several stages, namely inventory of legal materials, classification of legal materials, systematization of legal materials and verification of legal materials after which it is analyzed in a qualitative descriptive manner. The results of this study show that (1) the effectiveness of the implementation of the duties of the Pamong Praja Police Unit in controlling dormitories/lodging in Central Ende District, Ende Regency can be said to be effective, because the Satpol PP of Ende Regency in collaboration with other agencies carries out their duties and authorities following the existing procedures, even though the implementation is not perfect, (2) Obstacle factors for the implementation of Satpol PP's duties in ordering dormitories/lodgings, namely responsiveness and confrontation, compliance and understanding, limited resources, difficult cases and infrastructure constraints